Evaluación y clasificación de los alojamientos turísticos post-terremoto en la satisfacción del cliente del cantón Bolívar - Ulloa Cevallos, Karen Mishell (2021)
The objective of this work was to carry out an evaluation of post-earthquake tourist accommodation establishments in terms of customer satisfaction in the Bolívar canton; For this purpose, the main methodological reference was Prado & Rivera, 2010, and the MINTUR tourist accommodation categorization sheets and the SERVQUAL questionnaire were used as tools. The research was made up of 3 methodological phases through which the main results of the research were obtained; In this sense, phase I aimed to characterize the post-earthquake accommodation establishments in order to know the current situation of said offer, for which the Mintur characterization sheets were used; Phase II had the purpose of evaluating and classifying the accommodation offer to determine compliance with the legal regulations that regulate said sector through the Mintur categorization sheets and phase III had the objective of determining the level of satisfaction of the guests in function of the evaluation and classification of tourist accommodation establishments through the SERVQUAL questionnaire. As a result of the investigative process, it is concluded that the poor compliance with the requirements according to the category of accommodation establishments directly influences the degree of customer satisfaction; since the research shows a low quality service that affects customer satisfaction; a situation that is not the most favorable for the tourist reactivation of the sector after the last telluric event.